Faktor Faktor Yang Berhubungan dengan Penerimaan Vaksinasi Covid-19 pada Masyarakat di Kota Kupang Tahun 2022 - Yersintha Trisanlia Katarina; Apris A. Adu; Soleman Landi (Yayasan Literasi Sains Indonesia, 2023)
The global Covid-19 pandemic that continues to hit the world has infected and caused death to thousands of people. Vaccination is a method of preventinng disease in the world of health. Kupang City is one of the areas with the highest number of Covid-19 cases in the province of East Nusa Tenggara with the number of cases infected with Covid-19 as many as 15,446 cases. The vaccine that has been developed is the best hope as a solution to control the Covid-19 pandemic. The purpose of this study was to determine the factors related to the acceptance of the Covid-19 vaccination in the community in Kupang City in 2022. This research method was analytic observational with a cross sectional survey design with a sampling, namely accidental sampling. Respondents in this study were people in Kupang City aged 18 years and over totaling 369 people. Data analysis in this study used univariate and bivariate analysis with chi squaretest.. The results of this study indicate that the variables associated with acceeptance Covid-19 vaccination are age (p=0,007; CC=0,251), education (p=0,000; 0,298), knowledge (p=0,025; CC=0,130) and anxiety (p=0,000; CC =0,372). It is recommended for health institutions to plan a Covid-19 vaccination program so that it can reach all community targets and can optimize the control of Covid-19 in Kupang City.